Balancing Study and Paid Work: The Experiences of Construction Undergraduates in an Australian University (Construction Economics and Building, 2012)
A questionnaire survey was undertaken among third year studentsenrolled in the University of Melbourne’s Bachelor of Property andConstruction (BPC) programme. The survey explored students’experiences in balancing paid work with study. Hours spent in paidemployment were at least as long and, in many cases, were inexcess of hours spent at university. While work was not perceivedby students to pose a difficulty for attending lectures and tutorials,students indicated that their paid work made it difficult for them toengage in independent learning activities, such as using libraryresources or preparing for classes by reading beforehand. Twoscales, previously used in other countries to measure students’burnout and engagement, were tested. Both scales were foundto be valid and reliable in that the factorial structures foundin previous studies were confirmed and acceptable internalconsistency reliability coefficients were generated for each of thescales’ component factors. This opens the way for more in-depthmultivariate analysis to determine the linkages between workhours, work-study conflict and students’ burnout or engagementwith university life.